Law dissemination and education for ethnic minorities in mountainous areas in Vietnam - Quoc Suu, Nguyen (Nuances: Estudos sobre Educação, 2022)
The law dissemination and education for ethnic minority people in Vietnam is still facing challenges and suffering from shortcomings; hence, the effectiveness of law popularization is limited. Based on the aforementioned facts, this paper is dedicated to highlighting some important achievements in the law dissemination and education for the ethnic minorities, analyzing the drawbacks with the law dissemination and education for these populations and the causes of these drawbacks, and accordingly suggesting some radical solutions to the dissemination and education of law for ethnic minority people in Vietnam in the coming time. Thereby, the author proposes 4 groups of solutions in the coming time: First, improving professional capacity and skills for the contingent of legal reporters and propagandists who directly do legal education for people in ethnic minority and mountainous areas; Second, renewing the content of legal for these people; Third, innovating legal education methods; Fourth, reforming the form of legal education.